2016
DOI: 10.1264/jsme2.me15127
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil Fungal Populations and Communities to the Thinning of <i>Cryptomeria Japonica</i> Forests

Abstract: Forest management activities, such as tree thinning, alter forest ecology, including key components of forest ecosystems, including fungal communities. In the present study, we investigate the effects of forest thinning intensity on the populations and structures of fungal soil communities in the Cryptomeria japonica forests of central Taiwan as well as the dynamics of soil fungi communities in these forests after a thinning disturbance. Although the populations of soil fungi significantly increased in the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…These changes are associated with nutrient input from fresh litter, which occurs in temperate deciduous forests each autumn (Voříšková et al, 2014). In accordance with our study, Lin et al (2016) reported seasonal shifts of fungi in coniferous forests. The air and soil temperatures at both forest stands were higher in early summer, whereas the soil water content was increased in autumn (Table S6).…”
Section: Discussionsupporting
confidence: 93%
“…These changes are associated with nutrient input from fresh litter, which occurs in temperate deciduous forests each autumn (Voříšková et al, 2014). In accordance with our study, Lin et al (2016) reported seasonal shifts of fungi in coniferous forests. The air and soil temperatures at both forest stands were higher in early summer, whereas the soil water content was increased in autumn (Table S6).…”
Section: Discussionsupporting
confidence: 93%
“…Overby et al [2] also reported that the richness and abundance of soil bacterial communities, based on the phospholipid fatty acids method, were not affected 40 years after thinning treatment in a ponderosa pine (Pinus ponderosa) forest in the Southwestern United States, while the creation of clear-cut openings in forests increased the abundance and richness of AM fungal propagules. Several short-term studies have reported that soil microbial biomass and community structure are significantly altered one to five years after thinning treatments [18,65,67,68]. A recent meta-analysis of soil microbial biomass responses to forest disturbances indicated that partial harvesting (thinning) had no significant effect on soil bacterial and fungal biomass, while clear-cutting significantly reduced soil bacterial and fungal biomass [37].…”
Section: Microbial Diversity and Compositionmentioning
confidence: 99%
“…As we mentioned above, the improvement of soil fertility might be related to understory vegetation and litter input. Although many previous studies have reported the changes of soil physical [3,58,60], chemical [3,58], or biological [71,72] properties after thinning treatments, while they failed to evaluate the overall soil fertility status. Particularly, most of these studies mainly focused on carbon and nitrogen [73].…”
Section: Effect Of Thinning On Soil Chemical Propertiesmentioning
confidence: 99%